2007
DOI: 10.1667/rr0659.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Oxidative Clustered DNA Lesions in X-Irradiated Mouse Skin Tissues and Human MCF-7 Breast Cancer Cells

Abstract: Bistranded oxidative clustered DNA lesions are closely spaced lesions (1-10 bp) that challenge the DNA repair mechanisms and are associated with genomic instability. The endogenous levels of oxidative clustered DNA lesions in cells of human cancer cell lines or in animal tissues remain unknown, and these lesions may persist for a long time after irradiation. We measured the different types of DNA clusters in cells of two human cell lines, MCF-7 and MCF-10A, and in skin obtained from mice exposed to either 12.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…OCDLs were measured after digestion with enzymes that cleave the DNA at modified DNA residues, human APE1, which cleaves primarily at abasic sites, Escherichia coli EndoIII at oxypyrimidine sites, and human OGG1 at oxypurine sites (21). The number of sites was quantified by analysis of constant-field gel electrophoresis (22).…”
Section: Resultsmentioning
confidence: 99%
“…OCDLs were measured after digestion with enzymes that cleave the DNA at modified DNA residues, human APE1, which cleaves primarily at abasic sites, Escherichia coli EndoIII at oxypyrimidine sites, and human OGG1 at oxypurine sites (21). The number of sites was quantified by analysis of constant-field gel electrophoresis (22).…”
Section: Resultsmentioning
confidence: 99%
“…These lesions include DNA DSBs and non-DSB oxidative clustered DNA lesions (OCDL) [57,58]. For non-DSB oxidative clustered DNA lesions, both Monte Carlo simulation and experimental measurements using DNA base excision repair enzymes, such as DNA glycosylases and AP endonucleases isolated from E. Coli.…”
Section: Induction Of Dna Damage By High Let Radiationmentioning
confidence: 99%
“…Georgakilas and his team through collaborations with various elite research groups (ECU, NCI) have taken advantage of the properties of human repair enzymes OGG1 (oxidized purines), EndoIII (oxidized pyrimidines) and APE1 (abasic sites) in order to detect a variety of bistranded OCDLs in human and mouse tissues, using adaptations of DNA gel electrophoresis [4][5][6][7][8] . The concepts in DNA cluster quantification are simple, but their execution is technically and analytically demanding.…”
Section: Detection Of Ocdls In Vivo: Potential Clinical Applicationsmentioning
confidence: 99%
“…Dr. Georgakilas' group, using novel adaptations of DNA gel electrophoresis, has been able to provide to the scientific community relatively easy and reliable methodologies for the detection of OCDLs in a variety of cell and tissues [3,[9][10][11] . In early 2007, Gollapalle et al [4] showed for the first time in vivo that X-rays can induce a radiation-delayed effect in mice several weeks after the initial irradiation. In addition, they showed evidence of bystander or so-called distal effects [12] .…”
Section: Detection Of Ocdls In Vivo: Potential Clinical Applicationsmentioning
confidence: 99%